MODERN ASPECTS OF OPTIMIZING THE SURGICAL TREATMENT OUTCOMES OF ISCHEMIC MITRAL VALVE INSUFFICIENCY - Musayev, S.A. (World of Medicine and Biology, 2025)
The purpose of the study was to develop a clinical-diagnostic algorithm for determining surgical indications and choosing surgical methods for ischemic mitral valve insufficiency, aiming to improve short- and long-term outcomes. The two groups were involved: Group I (main) consisted of 132 patients who underwent surgery for ischemic mitral valve insufficiency between 2014 and 2020 using the proposed algorithm. Group II (comparison) consisted of 65 patients who underwent surgery for ischemic mitral valve insufficiency based on standard treatment protocols. In both groups, 79 % of patients were aged 51–60. Using identified potential predictors, an algorithm was developed to determine surgical indications and select the type of surgery for ischemic mitral valve insufficiency, which was then applied. According to results, over five years, survival in the algorithm group was 86.72 %, compared to 83.6 % in the comparison group (3.12 % lower). A comparative evaluation confirmed the effectiveness of the developed algorithm.